Sex change in scallop Patinopecten yessoensis: response to population composition? - Alla V. Silina (PeerJ, 2018)
Sex structure is very labile between populations and specific for each population because it is a result of genetic, ontogenetic and biocenotic influences on the mollusks. In this study, the age frequency distribution, age-sex structure, and sex ratio were assessed in the wild populations of the Yeso scallop Patinopecten yessoensis (Jay) observed at fifteen sites in the northwestern Sea of Japan (=East Sea). The sex ratio varied between the populations from 0.83:1 to 1.52:1 (males/females), with the mean sex ratio being 1.03 ± 0.05:1. Within a population, the proportions of males and females in term of number differed between age classes. Males were more numerous than females in the younger age classes, and females prevailed over males in the older age classes. It was found that in different scallop populations the sex change occurred at different ages. In the populations that predominantly consisted of young (two- to four-year-old) individuals, males prevailed over females in the age class 2 yr.; the equal male/female proportion was found in the age class 3 yr.; and in older age classes, females prevailed over males. Another pattern was observed in the populations that consisted mainly of middle-aged (five- to six-year-old) individuals. Here, the age-sex ratio became equal at an age of 4–6 years. In the old populations (mainly 6–12-year-olds) the equal male/female proportion was observed at an age of 8–10 years. Thus, the age of sex change was not uniform for the scallop populations. It depended on the age structure of the population and, thus, was socially controlled. The greater number of females in the older age classes suggests a protandric sex change.